Preparation method of novel nano-filler modified resin

By preparing yttrium oxide-doped zirconia sol and nanocluster powder, combined with nanoSiO2 filler and silane coupling agent, nanofiller modified resin was prepared, which solved the problem of complex and high cost of the existing dental filler nanocluster filler preparation process, and achieved high performance and low cost dental filler resin materials.

CN119700556APending Publication Date: 2025-03-28BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510005618.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The preparation process of existing dental filler nanocluster fillers is complex and costly, and the overall performance evaluation is insufficient, making it difficult to meet the domestic market's demand for stable and high-performance materials.

Method used

Zirconium acetate, yttrium nitrate, glacial acetic acid and water are used as raw materials, and yttrium oxide-doped zirconium oxide sol and nanocluster powder are prepared through high-temperature and high-pressure reaction and calcination. Compound fillers are prepared by heating, rotary evaporation and drying, and finally mixed with the mixed resin to prepare nanofilter modified resin.

Benefits of technology

The prepared nanofiller modified resin has high hardness, strong bending strength and excellent compressive strength. It is suitable for large-scale production. The raw materials are safe and non-toxic, low-cost, simple process, easy to control the reaction process, and low synthesis temperature.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of novel nanofiller modified resin, and belongs to the technical field of medical materials, yttrium oxide-doped zirconium oxide sol prepared from zirconium acetate and yttrium nitrate is used as a basic raw material, and zirconium oxide and silicon oxide nanocluster powder with stable yttrium oxide is prepared by matching with silicon dioxide sol and calcining. The preparation method comprises the following steps: mixing the nanocluster powder and the nano-SiO2 filler, coupling with a silane coupling agent, drying, and uniformly mixing with mixed resin containing acrylic resin, a photoinitiator, an antioxidant, an anti-reducing agent, an ultraviolet absorbent and a coloring agent to obtain the nanofiller modified resin. According to the preparation method of the novel nanofiller modified resin, the raw materials are safe, nontoxic and low in cost, the technological process is simple, the reaction process is easy to control, and the synthesis temperature is low. The prepared nano-filler modified resin is high in hardness, high in bending strength, excellent in compressive strength and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical materials, and in particular to a method for preparing a novel nano-filler modified resin. Background Art

[0002] The main components of dental filling resins are inorganic fillers, organic fillers and ceramic fillers. Inorganic fillers mainly include silicates, aluminosilicates, glass powder, etc. The preparation process of inorganic fillers is relatively complicated and the cost is high, which limits their wide application. Organic fillers mainly include polymer particles, nanocellulose, etc. The physical properties and chemical stability of organic fillers are relatively poor, and they are easily affected by external factors and age. Ceramic fillers mainly include oxides, non-oxides, etc. Oxide fillers such as aluminum oxide, silicon oxide, zirconium oxide, etc. have high strength and high hardness, and are suitable for occasions such as posterior tooth restorations that require large bite forces. Non-oxide fillers such as silicon nitride and silicon carbide have excellent wear resistance and chemical stability, and are suitable for occasions such as anterior tooth aesthetic restorations that require beauty and long-term stability. Ceramic fillers have high strength and high hardness, and can provide good wear resistance and chemical stability.

[0003] Nanocluster fillers for dental filling resins are a new type of filler with excellent physical properties and biocompatibility. This filler is composed of nanoscale particles and is usually in the form of nanocomposites or nanoparticle-reinforced materials. Compared with micro-hybrid, micro-filling or nano-hybrid systems, "nanoclusters" provide a unique reinforcement mechanism that can significantly improve the strength and reliability of materials under various environmental storage and testing conditions. Due to the small particle size of nanocluster fillers, the wear resistance and strength of dental filling resins can be significantly improved, thereby extending the service life of the fillings. In addition, nanocluster fillers have a small particle size and a large specific surface area, which can not only effectively fill the subtle defects on the tooth surface, making the repaired teeth smoother and more beautiful, but also better adapt to the morphology and structure of the tooth surface, making the filling operation easier and faster. Nanocluster fillers are usually prepared with materials with good biocompatibility, which can be well compatible with human tissues and reduce the risk of irritation and allergic reactions to human tissues.

[0004] 3M has been developing nano and nanocluster fillers for a long time. The zirconium-silicon nanoparticles were synthesized using silica colloidal solution and zirconium-based salts to form nanoclusters with an average particle size of 0.6 μm. Mitra SB et al. published an article titled "An application of nanotechnology in advanced dental materials" in The Journal of the American Dental Association in 2003. The study found that the structure of nanoclusters effectively improved the wear resistance and gloss retention of resin materials and had a positive effect on crack propagation resistance. Ruili Wang et al. published an article titled "Wear behavior of light-cured resin composites with bimodal silica nanostructures as fillers" in Materials Science and Engineering in 2013. They prepared nanosilicon nanoclusters with a particle size of 0.07-2.70 μm by surface modification of nanosilicon dioxide. The silanized nanostructures containing silicon nanoparticles and nanoclusters were used as co-fillers, and the wear resistance of the obtained resin composites was significantly improved. In 2020, Jiexin Wang et al. published an article titled "The properties of dental resin composites reinforced with silica colloidal nanoparticle clusters: Effects of heat treatment and filler composition" in Composites Part B: Engineering. They used spray drying to prepare silica colloidal nanoparticle clusters, strengthened the structure by calcination, and improved the comprehensive performance of dental resin materials by combining them with different fillers.

[0005] Although nanocluster fillers have many advantages, there are few studies on the preparation of dental filling resins with nanocluster fillers, and the research in various aspects is not sufficient, especially the evaluation of the overall performance of resin materials. In addition, the domestic market is mainly dominated by foreign products, and there is an urgent need for industrially produced, stable, and high-performance technologies. Summary of the invention

[0006] The purpose of the present invention is to provide a novel method for preparing a nanofiller modified resin, wherein the raw materials are safe, non-toxic and low in cost, the process is simple, the reaction process is easy to control and the synthesis temperature is low. The prepared nanofiller modified resin has high hardness, high bending strength and excellent compressive strength and is suitable for large-scale production.

[0007] To achieve the above object, the present invention provides a method for preparing a novel nanofiller modified resin, comprising the following steps: S1, zirconium acetate, yttrium nitrate, glacial acetic acid and water are mixed, stirred evenly and then added into a high-pressure reactor, and a high-temperature and high-pressure reaction is carried out under stirring. After the reaction is completed, the mixture is filtered to obtain a yttrium oxide-doped zirconium oxide sol; S2, adjusting the pH of the silica sol to below 1.2 with nitric acid, and removing Na ions in the silica sol with an ion exchange resin to obtain product A; S3, adding yttria-doped zirconium oxide sol to product A, and obtaining nanocluster powder through calcination, grinding and sieving; S4, adding nano-SiO2 filler to the nano-cluster powder, placing the mixed filler in a flask, adding a silane coupling agent, ethyl acetate and ammonia water, heating, rotary evaporation and drying to obtain a composite filler; S5. Add the composite filler into the mixed resin, and mix them evenly using a three-roller grinder to obtain a nano-filler modified resin.

[0008] Preferably, in S1, the molar ratio of yttrium nitrate to zirconium acetate is (0.03-0.08):1; The molar ratio of zirconium acetate to glacial acetic acid is 1:(0.5-1.5); The mass ratio of zirconium acetate to water is 1:(1-3).

[0009] Preferably, in S1, the high temperature and high pressure reaction temperature is 180-300°C, and the high temperature and high pressure reaction time is 4-50h.

[0010] Preferably, in S3, the calcination temperature is 650-800° C., and the calcination time is 1-4 h.

[0011] Preferably, in S3, the particle size of the nanocluster powder is 10-70 um.

[0012] Preferably, in S4, the particle size of the nano-SiO2 filler is 20 nm, and the nano-SiO2 filler accounts for 5-12.5% ​​of the mass of the mixed filler.

[0013] Preferably, in S4, the heating reaction temperature is 70-90° C., and the heating reaction time is 2-4 h; The reduced pressure is 0.1-0.2MPa, the rotary evaporation temperature is 40-50°C, and the rotary evaporation time is 0.5-1h.

[0014] Preferably, in S4, the drying temperature is 90-100° C. and the drying time is 2-4 h.

[0015] Preferably, in S5, the composite filler accounts for 70-80% of the mass of the novel nanofiller modified resin.

[0016] Preferably, in S5, the mixed resin includes acrylic resin, photoinitiator, antioxidant, anti-reducing agent, ultraviolet absorber and colorant.

[0017] Therefore, the present invention adopts the above-mentioned novel method for preparing nanofiller modified resin, which has the following beneficial effects: (1) The raw materials used are low-cost and readily available, and the production process is simple and energy-efficient. The raw materials used are all cheap chemical raw materials that are readily available on the market. The production process is only a simple calcination process, which is lower in preparation cost than spray drying, surface modification and other processes.

[0018] (2) Nanocluster powders have high biocompatibility, which can reduce the risk of irritation and allergic reactions to human tissues. In addition, their small particle size can improve the wear resistance and polishing properties of dental filling resins and extend the service life of the material.

[0019] (3) The proportion of composite fillers in nanofiller modified resin is relatively high, which makes the nanofiller modified resin have relatively excellent mechanical properties, namely high hardness, high bending strength and high compressive strength.

[0020] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further illustrated by the following examples.

[0022] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0023] Embodiment 1 A method for preparing a novel nanofiller modified resin comprises the following steps: S1. Add 200g of 15% (measured in zirconium) zirconium acetate to 170mL of deionized water, add 6.6g of yttrium nitrate hexahydrate and 20g of glacial acetic acid, and stir at room temperature for 30min. Then add to the autoclave, continue stirring, and react at 250℃ for 5h. After the reaction is completed, filter through an organic membrane to obtain yttrium oxide-doped zirconium oxide sol; S2, adjusting the pH of commercial acidic silica sol (30 wt% SiO2) to below 1.2 with nitric acid, and removing Na ions in the silica sol with ion exchange resin to obtain product A; S3, adding 100 g of yttria-doped zirconium oxide sol to 94 g of product A, and calcining at 710° C. for 1 h. Grinding and sieving the solid obtained after calcination to obtain nanocluster powder with a particle size of 2 μm; S4, take 2g of nano-SiO2 filler and 38g of nano-cluster powder and mix them, the mass of nano-SiO2 filler accounts for 5% of the mass of the mixed filler. Put 40g of the mixed filler in a flask, add 6.02g of GF-3 silane coupling agent (domestic number KH570), 49g of ethyl acetate and 0.76g of 30% ammonia water, and adjust the pH of the mixture to 8.75. React the resulting solution at 80°C for 3h, remove the solvent by rotary evaporation, and then dry at 90°C for 30min to obtain a composite filler; S5. Add the composite filler to the mixed resin and mix them evenly using a three-roll grinder to obtain a nanofiller modified resin. The composite filler accounts for 77% of the mass of the nanofiller modified resin. The mixed resin includes 24.1wt% of bisphenol A propylene glycol dimethacrylate (Bis-GMA), 33.8wt% of ethoxylated bisphenol A methacrylate diester (Bis-EMA6), 33.8% of methacrylate carbamate (UDMA), 3.7wt% of polyethylene glycol dimethacrylate (PEGDMA) (molecular weight 400-600), 1.1wt% of triethylene glycol dimethacrylate (TEDMA), and 1.1wt% of bisphenol A propylene glycol dimethacrylate (Bis-GMA). The raw materials were prepared from the following materials: GDMA), 0.15wt% DL-camphorquinone (CPQ), 0.25wt% phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), 0.4wt% UV absorber N-(ethoxycarbonylphenyl)-N'-methyl-N'-phenylformamidine (UV-1), 1.2wt% 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, 1.4wt% antioxidant BHT and 0.1wt% ferric oxide.

[0024] Embodiment 2 A method for preparing a novel nanofiller modified resin comprises the following steps: S1. Add 200g of 15% (measured in zirconium) zirconium acetate to 170mL of deionized water, add 6.6g of yttrium nitrate hexahydrate and 20g of glacial acetic acid, and stir at room temperature for 30min. Then add to the autoclave, continue stirring, and react at 250℃ for 5h. After the reaction is completed, filter through an organic membrane to obtain yttrium oxide-doped zirconium oxide sol; S2, adjusting the pH of commercial acidic silica sol (30 wt% SiO2) to below 1.2 with nitric acid, and removing Na ions in the silica sol with ion exchange resin to obtain product A; S3, adding 100 g of yttria-doped zirconium oxide sol to 94 g of product A, and calcining at 710° C. for 1 h. Grinding and sieving the solid obtained after calcination to obtain nanocluster powder with a particle size of 2 μm; S4, take 3g of nano-SiO2 filler and 37g of nano-cluster powder and mix them, the mass of nano-SiO2 filler accounts for 7.5% of the mass of the mixed filler. Put 40g of the mixed filler in a flask, add 6.02g of GF-3 silane coupling agent (domestic number KH570), 49g of ethyl acetate and 0.76g of 30% ammonia water, and adjust the pH of the mixture to 8.75. React the resulting solution at 80°C for 3h, remove the solvent by rotary evaporation, and then dry at 90°C for 30min to obtain a composite filler; S5. Add the composite filler to the mixed resin and mix them evenly using a three-roll grinder to obtain a nanofiller modified resin. The composite filler accounts for 75% of the mass of the nanofiller modified resin. The mixed resin includes 24.1wt% of bisphenol A propylene glycol dimethacrylate (Bis-GMA), 33.8wt% of ethoxylated bisphenol A methacrylate diester (Bis-EMA6), 33.8% of methacrylate carbamate (UDMA), 3.7wt% of polyethylene glycol dimethacrylate (PEGDMA) (molecular weight 400-600), 1.1wt% of triethylene glycol dimethacrylate (TEDMA), and 1.1wt% of bisphenol A propylene glycol dimethacrylate (TEDMA). The raw materials were prepared from the following materials: GDMA), 0.15wt% DL-camphorquinone (CPQ), 0.25wt% phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), 0.4wt% UV absorber N-(ethoxycarbonylphenyl)-N'-methyl-N'-phenylformamidine (UV-1), 1.2wt% 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, 1.4wt% antioxidant BHT and 0.1wt% ferric oxide.

[0025] The difference from the first embodiment is that the mass of the nano-SiO2 filler accounts for 7.5% of the mass of the mixed filler, and the mass of the composite filler accounts for 75% of the mass of the nano-filler modified resin.

[0026] Embodiment 3 A method for preparing a novel nanofiller modified resin comprises the following steps: S1. Add 200g of 15% (measured in zirconium) zirconium acetate to 170mL of deionized water, add 10.6g of yttrium nitrate hexahydrate and 20g of glacial acetic acid, and stir at room temperature for 30min. Then add to the autoclave, continue stirring, and react at 250℃ for 5h. After the reaction is completed, filter through an organic membrane to obtain yttrium oxide-doped zirconium oxide sol; S2, adjusting the pH of commercial acidic silica sol (30 wt% SiO2) to below 1.2 with nitric acid, and removing Na ions in the silica sol with ion exchange resin to obtain product A; S3, adding 100 g of yttria-doped zirconium oxide sol to 94 g of product A, and calcining at 725° C. for 2 h. Grinding and sieving the solid obtained after calcination to obtain nanocluster powder with a particle size of 2 μm; S4, take 2g of nano-SiO2 filler and 38g of nano-cluster powder and mix them, the mass of nano-SiO2 filler accounts for 5% of the mass of the mixed filler. Put 40g of the mixed filler in a flask, add 6.02g of GF-3 silane coupling agent (domestic number KH570), 49g of ethyl acetate and 0.76g of 30% ammonia water, and adjust the pH of the mixture to 8.75. React the resulting solution at 80°C for 3h, remove the solvent by rotary evaporation, and then dry at 90°C for 30min to obtain a composite filler; S5, adding the composite filler to the mixed resin, and mixing them evenly using a three-roll grinder to obtain a nanofiller modified resin. The composite filler accounts for 77% of the mass of the nanofiller modified resin, and the mixed resin includes 24.1wt% of bisphenol A propylene glycol dimethacrylate (Bis-GMA), 33.8wt% of ethoxylated bisphenol A methacrylate diester (Bis-EMA6), 33.8% of methacrylate carbamate (UDMA), 3.7wt% of polyethylene glycol dimethacrylate (PEGDMA) (molecular weight 400-600), 1.1wt% of triethylene glycol dimethacrylate ( The raw materials were prepared from the following materials: TEGDMA), 0.15wt% DL-camphorquinone (CPQ), 0.25wt% N,N'-dimethylaminoethyl methacrylate (DMAEMA), 0.4wt% UV absorber N-(ethoxycarbonylphenyl)-N'-methyl-N'-phenylformamidine (UV-1), 1.2wt% 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, 1.4wt% antioxidant BHT and 0.1wt% ferric oxide.

[0027] Different from Example 1, the ratio of yttrium nitrate to zirconium acetate is adjusted, the calcination temperature and calcination time of the mixture of sol and product A are increased, and the photoinitiator in the mixed resin is replaced.

[0028] Comparative test 1 The Vickers microhardness of the nanofiller modified resin prepared in Example 1 and Example 2 was measured under a load of 50g using a microhardness tester for 10s. The Vickers hardness of Example 1 was 89HV, and the Vickers hardness of Example 2 was 80HV. The results show that the nanofiller modified resin in Example 1 is more compact in microstructure and has better wear resistance and scratch resistance. According to ISO 4049: 2009 test, the curing depth of Example 1 is 5mm, and the curing depth of Example 2 is 6mm. According to ISO 4049: 2009, the bending strength is measured, and Example 1 is about 140MPa, and Example 2 is about 149MPa. Example 1 is slightly lower than Example 2 in curing depth and bending strength, but the difference is not large, and both materials perform well. According to ISO9917-1, the compressive strength is measured, and Example 1 is about 370MPa, and Example 2 is about 356MPa. The results show that the compressive strength of Example 1 is more excellent.

[0029] In summary, the nanofiller-modified resin prepared in Example 1 exhibits higher Vickers microhardness, can provide excellent wear resistance and scratch resistance, thereby effectively extending the service life; at the same time, its excellent compressive strength enables it to better withstand chewing force and reduce the damage of the material under compressive stress. Therefore, the conditions of Example 1 are more suitable for dental resins.

[0030] Therefore, the present invention adopts the above-mentioned novel method for preparing a nanofiller modified resin, the raw materials are safe and non-toxic and the cost is low, the process flow is simple, the reaction process is easy to control, and the synthesis temperature is low. The prepared nanofiller modified resin has high hardness, high bending strength, excellent compressive strength, and is suitable for large-scale production.

[0031] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a novel nanofiller modified resin, characterized in that: The following steps are involved: S1, zirconium acetate, yttrium nitrate, glacial acetic acid and water are mixed, stirred evenly and then added into a high-pressure reactor, and a high-temperature and high-pressure reaction is carried out under stirring. After the reaction is completed, the mixture is filtered to obtain a yttrium oxide-doped zirconium oxide sol; S2, adjusting the pH of the silica sol to below 1.2 with nitric acid, and removing Na ions in the silica sol with an ion exchange resin to obtain product A; S3, adding yttria-doped zirconium oxide sol to product A, and obtaining nanocluster powder through calcination, grinding and sieving; S4, adding nano-SiO2 filler to the nano-cluster powder, placing the mixed filler in a flask, adding a silane coupling agent, ethyl acetate and ammonia water, heating, rotary evaporation and drying to obtain a composite filler; S5. Add the composite filler into the mixed resin, and mix them evenly using a three-roll grinder to obtain a novel nano-filler modified resin.

2. The preparation method according to claim 1, characterized in that: In S1, the molar ratio of yttrium nitrate to zirconium acetate is (0.03-0.08):1; The molar ratio of zirconium acetate to glacial acetic acid is 1:(0.5-1.5); The mass ratio of zirconium acetate to water is 1:(1-3).

3. The preparation method according to claim 1, characterized in that: In S1, the high temperature and high pressure reaction temperature is 180-300°C, and the high temperature and high pressure reaction time is 4-50h.

4. The preparation method according to claim 1, characterized in that: In S3, the calcination temperature is 650-800°C, and the calcination time is 1-4h.

5. The preparation method according to claim 1, characterized in that: In S3, the particle size of the nanocluster powder is 10-70 um.

6. The preparation method according to claim 1, characterized in that: In S4, the particle size of the nano-SiO2 filler is 20 nm, and the nano-SiO2 filler accounts for 5-12.5% ​​of the mass of the mixed filler.

7. The preparation method according to claim 1, characterized in that: In S4, the heating reaction temperature is 70-90°C and the heating reaction time is 2-4h; The reduced pressure is 0.1-0.2MPa, the rotary evaporation temperature is 40-50°C, and the rotary evaporation time is 0.5-1h.

8. The preparation method according to claim 1, characterized in that: In S4, the drying temperature is 90-100°C and the drying time is 2-4h.

9. The preparation method according to claim 1, characterized in that: In S5, the composite filler accounts for 70-80% of the mass of the nanofiller-modified resin.

10. The preparation method according to claim 1, characterized in that: In S5, the mixed resin includes acrylic resin, photoinitiator, antioxidant, anti-reducing agent, ultraviolet absorber and colorant.